Evaluating dietary habits of adults and their relationship with sleep quality in the Kingdom of Saudi Arabia - Alghamdi, Nouf A.; Almasaudi, Arwa S. (Frontiers in Nutrition, 2025)
IntroductionSleep plays a vital role in daily functioning and well-being, yet insufficient sleep is a growing global concern influenced by modern lifestyles.MethodsThis study examined the relationship between dietary habits, and sleep quality among 1,041 Saudi adults using self-administered questionnaires, including the Pittsburgh Sleep Quality Index (PSQI) and a nutrition behavior questionnaire.ResultsThe key findings included that 77.4% of participants had poor sleep quality (PSQI > 6). Females reported worse sleep efficiency, more disturbances, and greater daytime dysfunction than males. Dietary patterns revealed low consumption of fruits (38.2%), vegetables (28%), fish (38.9%), and legumes (38%), and high consumption of starches (41%), poultry (26.4%), and sweets (29.9%). Positive associations were found between sleep efficiency and fruit, fish, and legume intake, while high starch, sweets, and dairy consumption correlated with poorer sleep quality, longer sleep latency, and increased daytime dysfunction. Gender-specific analysis showed distinct dietary effects. In males, fruits, vegetables, dairy, and legumes improved sleep quality, whereas starches and sweets negatively affected it. In females, sweets negatively affected sleep quality and latency, while fish consumption improved sleep efficiency and reduced dysfunction.DiscussionThe study highlights the connection between diet and sleep, suggesting that individualized dietary interventions could help enhance sleep quality. However, limitations, such as self-reported data and confounding factors, call for further research using objective measures.